A Simple Upper Limb Rehabilitation Trainer - Abdul Rahman, Hisyam (International Journal of Integrated Engineering, 2017)
Stroke is the leading cause of disability. Reaching movement including shoulder and elbow movements is the most important movement for many daily activities routine. To maximize functional recovery, stroke survivors go through rehabilitation sessions, under the supervision of physiotherapists in hospitals. Unfortunately, physiotherapy is generally limited to only a few hours per week and labor-intensive. There are many robotic devices have been developed to overcome this problem. However, the cost of rehabilitation robots is still a common problem, limiting their cost-benefit profile and making evaluating and implementing them on a large scale difficult. This paper presents the simple, compact and low cost interactive rehabilitation module for upper limb rehabilitation purposes. This module is intended to be used for training of shoulder and elbow movements integrated with game like virtual reality system.